PENGARUH RESTRUKTURISASI ORGANISASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA PADA APARATUR SIPIL NEGARA FUNGSIONAL DI LINGKUNGAN BALAI BESAR GURU PENGGERAK PROPINSI JAWA TIMUR - Slamet Muharyono; Nugroho Mardi Wibowo (MAP (Jurnal Manajemen dan Administrasi Publik), 2023)
The research aims to analyze the effect of mutation and career development with employee performance attachment variables, whether education and career development variables have on employee performance with employee job satisfaction as an intervening variable. This research uses quantitative descriptive methods. The number of samples in this study was 126 respondents who were employees of the East Java Provincial Center for Teacher Mobilization. The data collection technique is by administering a questionnaire with a Partial Least Square (PLS) data processing tool based on Structural Equation Model (SEM) version 4.0. The results of this research show that organizational structuring, career development and job satisfaction have a direct effect on employee performance. Apart from that, organizational organization and career development also have a direct effect on employee performance through job satisfaction.